2018
DOI: 10.3390/ijms19030799
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Weaknesses of Pre-Clinical Models for Human Melanoma Treatment: Dawn of Dogs’ Revolution for Immunotherapy

Abstract: Despite several therapeutic advances, malignant melanoma still remains a fatal disease for which novel and long-term curative treatments are needed. The successful development of innovative therapies strongly depends on the availability of appropriate pre-clinical models. For this purpose, several mouse models holding the promise to provide insight into molecular biology and clinical behavior of melanoma have been generated. The most relevant ones and their contribution for the advancement of therapeutic appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 151 publications
(182 reference statements)
0
40
0
Order By: Relevance
“…For melanomas, obvious unmet needs remain to better manage, treat, and prevent this disease, considering their numerous specific subtypes. To this end, recent reviews have demonstrated the strength of spontaneous canine melanomas as relevant genetic and therapeutic models for specific human melanoma subtypes [18,21,31,32,33,34,35].…”
Section: Comparative Oncology Model Specificitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…For melanomas, obvious unmet needs remain to better manage, treat, and prevent this disease, considering their numerous specific subtypes. To this end, recent reviews have demonstrated the strength of spontaneous canine melanomas as relevant genetic and therapeutic models for specific human melanoma subtypes [18,21,31,32,33,34,35].…”
Section: Comparative Oncology Model Specificitiesmentioning
confidence: 99%
“…Canine melanomas also occur in the haired skin, nail bed, footpad, eye (Figure 1), gastro-intestinal tract, central nervous system, or muco-cutaneous junction [37,38,41], and it is well known that prognosis greatly depends on tumor location (Figure 2 and Figure 3); oral melanomas presenting the worse prognosis with a median survival time (MST) of 6 months, whereas MST was not reached in cutaneous forms. Digital forms seem to have intermediate prognosis, with an MST of 11.8 months [30,32,33,34,35,36,37]. Melanoma is a tumor of older dogs, with no sex predilection, but some breeds are more prone to develop a specific melanoma subtype [18,34,42,43,44].…”
Section: Canine Melanomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in our understanding of cutaneous melanoma have been facilitated by a range of animal models, which have helped to delineate not only the basic biology of the disease, but also the role of driver genes, and the mechanisms of response and resistance to targeted therapies 1113 . In the context of mucosal melanoma, the most widely accepted animal model is canine melanoma, which bears histological similarities to the human disease and generally develops in the oral mucosa 14 . Dogs have been used extensively to explore the role of new therapies such as vaccination for disease management, but with the exception of analysing driver genes such as BRAF and NRAS , little is known about the genetic landscape of this malignancy and how canine and human mucosal melanomas compare 13,1517 .…”
Section: Introductionmentioning
confidence: 99%
“…The canine model of cancer is considered an excellent model for human translation [66][67][68][69]. Thus, we employed companion canines recruited to the Western College of Veterinary Medicine at the University of Saskatchewan with treatment resistant lymphoma into our study to reveal the gene expression differences between tumors with variable treatment responsivenesses, as well as to determine the effects of metformin on cancer progression in these animals.…”
Section: Discussionmentioning
confidence: 99%